A funfair without the candy floss: engaging communities to prevent diabetes in Nepal. (April 2021) - Morrison, J.; Arjyal, A.
Abstract: Objectives: The World Health Organization estimates that 422 million people have diabetes, three-quarters of whom live in low- and middle-income countries. Global action plans to address non-communicable diseases (NCDs) recognise the centrality of community engagement to create an enabling environment within which to address risk factors. Study design: In this article, we describe and critically reflect on a cocreated community engagement approach to address type 2 diabetes in the southern plains of Nepal. We coproduced the engagement approach with 40 artists from the Janakpur Women's Development Centre to create an environment for dialogue about diabetes and NCD risk between artists and the general public. Methods: We used participatory action research to produce contextually relevant interactive methods and materials. Methods included artists' peer research to inform creative workshops, a drama performed in 19 villages and a two-day funfair in a public park. We used qualitative and participatory methods to analyse the effect of this engagement and reflect on lessons learned. Results: Around 2000 people saw the drama, and around 4000 people attended the funfair. Community dialogue about prevention of diabetes was facilitated by drama and through games and songs at the funfair. Artists grew confident to interact with their peers and drama audiences about the causes of diabetes and prevention strategies. Despite crowds at the funfair, it was difficult to reach women because the venue was often used by men and boys, and patriarchal norms prevent women from free movement. Village interactions were able to engage a more mixed audience. Conclusion: Innovative, asset-based community engagement about diabetes and other NCDs at scale is possible through locating, building on and strengthening community resources to address local health issues. Engagement could be enhanced by considering the gendered nature of community engagement spaces and by increasing opportunities for interaction between artists and the general public through more intimate and large-scale events. Highlights: There is a need for innovative approaches to engage with communities to prevent and control non-communicable diseases. We coproduced a population-based community engagement approach with artists in southern Nepal using peer research, a community drama and a two-day funfair in a public park. We successfully engaged with more than 4000 people who enjoyed our creative art-based approach, which stimulated dialogue about diabetes among artists and the general public. Innovative, asset-based community engagement at scale is possible through locating, building on and strengthening community resources to address local health issues, creating empowered communities. Engagement could be enhanced by considering the gendered nature of public engagement spaces and by increasing opportunities for interaction between artists and the general public through more intimate and large-scale events.